Analisis potensi sektor unggulan dan pemetaan kemiskinan masyarakat di Wilayah Maminasata Sulawesi Selatan - Citra Ayni Kamaruddin; Syamsu Alam (Seminar Nasional LP2M UNM, 2019)
The results of the study show that there is still a high level of disparity in the leading sectors in the Mamminasata region. Based on leading sector analysis tools Location Quotient Analysis (LQ), Growth Ratio Model Analysis (MRP), Overlay Analysis, shows that Makassar City has 12 leading sectors, Gowa, 7 leading sectors, Maros 4 superior sector, and Takalar 3 superior sector. While the results of the Klassen Typology analysis show that only Makassar City consistently shows 12 superior sectors are in quadrant I (advanced and fast-growing sectors). While other regencies are only 3 sectors which are in quadrant I, other economic sectors are growing but depressed, there are also potential ones. In fact, Maros and Takalar have 11 sectors that are still lagging behind. Based on the poverty mapping of the districts / cities in the Mamminasata area, it shows that the cities of Makassar and Gowa have an average number of poor people lower than the province of South Sulawesi. Takalar Regency coincides or tends to be the same as South Sulawesi province. Whereas Maros is above the SULSEL poverty average. Even so, the average economic growth of the city in the Mamminasata area is higher than that in. South Sulawesi. There is a paradoxical symptom between the GRDP rate and poverty. In aggregate poverty in the Mamminasata area has declined during the study period. Makassar City, Gowa and Maros, although the rate of growth has declined, the number of poor people has also declined. Whereas Takalar District has an increased GRDP rate but its poverty also increases